PENGARUH HARGA DAN DAYA TARIK IKLAN TERHADAP MINAT BELI JASA EKSPEDISI PAXEL SURABAYA - Alan Wahyu Setiawan; Handy Aribowo (Universitas Dharmawangsa, 2023)
Delivery or logistics services are one of the business fields that is currently growing. Its development cannot be separated from the rise of online shopping trends. Paxel is a technology-based long-distance delivery service company. Today's consumers have many choices to use delivery or logistics services in their purchase transactions. Various factors can drive consumer buying interest to use delivery services. This study aims to prove the effect of price and advertising attractiveness on consumer buying interest in using Paxel shipping services in Surabaya. The research population is all users of Paxel logistics services in Surabaya. Based on the simple random sampling technique, a sample of 100 people was taken. The data analysis technique uses multiple linear regression analysis, coefficient of determination, t test and F test. The conclusion from this study is that price influences consumer buying interest. Advertising attractiveness affects consumer buying interest. Price and advertising simultaneously influence consumer buying interest. The suggestion from this research is that Paxel shipping companies should continue to monitor the prices offered by competitors in the shipping industry and adjust the prices offered to remain competitive. Paxel shipping companies should provide promotional offers or special discounts to loyal customers or new customers, this can help increase buying interest and strengthen customer loyalty.